Research of New Transmission Mechanism and Its Application in Pedal Drying Barrel - Zhang Zhixin; Liu Yuekun; Wang Jianwei; Guan Daxin; Zhou Jianhui; Chai Ying (Jixie chuandong)
Students in general can’t use high-power electrical appliances to dry clothes. And there is a few defects in the existing research on manpower machinery in the design of human waste drum. A new type of transmission device which can freely change the transmission ratio named cone shaped winding shaft is designed innovatively. And it is applied to the overall design of the foot-type drying barrel. Through the analysis of the taper movement process and the prototype of the test,the results show that it is feasible to apply the cone shaped winding shaft to the pedal,the work efficiency is improved dramatically. The performance of the drying barrel is optimized and easy to use. The restrictions on high-power electricity is relieved. It has large application value for the students group and the persons committed to energy conservation and environmental protection.